Glass ceramic and chemically strengthened glass, and method for producing same
By heating bending and crystallizing the amorphous glass, combined with chemical strengthening technology, the challenges of three-dimensional crystalline glass in terms of strength, transparency and shape stability are solved, and excellent glass performance is achieved.
Patent Information
- Application Number
- CN202311363136.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2019-04-05
- Filing Date
- 2020-03-13
- Publication Date
- 2025-02-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, when manufacturing three-dimensional crystal glass, problems of stress difference and transparency are prone to occur, and it is difficult to achieve excellent strength, transparency and shape stability.
By heating and bending the amorphous glass, a three-dimensional shape amorphous glass with a specific R shape is obtained, and crystallized by heating treatment to form an excellent three-dimensional shape microcrystalline glass. The method involves performing two steps of heating treatment within a specific temperature range and forming a compressive stress layer using ion exchange techniques during chemical reinforcement.
The high strength, excellent transparency and good shape stability of three-dimensional glass are achieved, and the problems of poor stress and reduced transparency are avoided.
Smart Images

Figure CN119409418A_ABST
Abstract
Description
[0001] This application is a divisional application of the Chinese patent application with application date of March 13, 2020 and application number 202080026030.3. Technical Field
[0002] The present invention relates to a three-dimensionally shaped glass-ceramic and chemically strengthened glass having high transparency and excellent strength and formability, and a method for producing the same. Background Art
[0003] The cover glass of display devices of mobile devices such as mobile phones and smartphones, and the cover glass of vehicle-mounted display components such as instrument panels and head-up displays (HUDs) are required to have excellent strength and transparency. For example, thin and high-strength chemically strengthened glass is used as such cover glass.
[0004] As the glass used for the above-mentioned protective glass, in order to improve operability and visual recognition, a three-dimensional glass composed of a plurality of R shapes is sometimes required. As a method for manufacturing a three-dimensional glass, for example, a method of bending a flat glass plate by heating and pressing it with a forming mold (also called three-dimensional forming) can be cited (Patent Document 1).
[0005] In addition, as glass used for the above-mentioned protective glass, amorphous glass containing no crystals is used, but microcrystalline glass having higher strength has also been proposed (Patent Document 2). Microcrystalline glass is glass obtained by heat-treating glass to precipitate crystals in the glass.
[0006] As methods for obtaining microcrystalline glass in a three-dimensional shape, for example, there are: a method of bending amorphous glass while causing crystals to precipitate, a method of bending amorphous glass after crystallizing it, a method of processing microcrystalline glass into a three-dimensional shape by grinding or the like, a method of bending amorphous glass and then crystallizing it, etc. (Patent Documents 3 and 4).
[0007] Patent document 2 discloses a method for manufacturing microcrystalline glass having a curved surface shape, wherein the method for manufacturing microcrystalline glass has a deformation step: maintaining the temperature of the plate-shaped glass so that it is within a first temperature range, while allowing crystals to precipitate from the above-mentioned plate-shaped glass, at least a portion of the above-mentioned plate-shaped glass is deformed into a curved surface shape by applying an external force to the above-mentioned plate-shaped glass.
[0008] In addition, patent document 3 discloses a method for manufacturing a microcrystalline glass curved plate, wherein the method for manufacturing a microcrystalline glass curved plate comprises: a process for making a crystalline glass curved plate and a crystallization process, wherein the process for making a crystalline glass curved plate is to locally heat a portion of a crystalline glass flat plate in one direction so that the crystalline glass flat plate is deformed in a softened state; and the crystallization process is to place the crystalline glass curved plate on a forming mold and heat it so that the crystalline glass curved plate is crystallized while being deformed, thereby obtaining the microcrystalline glass curved plate.
[0009] Prior art literature
[0010] Patent Literature
[0011] Patent Document 1: International Publication No. 2014 / 167894
[0012] Patent Document 2: International Publication No. 2019 / 022034
[0013] Patent Document 3: Japanese Patent Application Publication No. 2017-190265
[0014] Patent Document 4: Japanese Patent Application Publication No. 2014-141356 Summary of the invention
[0015] Problems to be solved by the invention
[0016] As shown in Patent Document 1, in a method of manufacturing glass having a three-dimensional shape by bending, particularly in the bending portion, due to uneven contact between the glass and the forming mold, uneven heat is generated during heating, and stress difference (delay) is easily generated in the formed glass. In addition, when the cooling rate during bending is increased in order to improve productivity, the delay in the formed glass increases. When the delay in the glass increases, the glass is easily broken and the strength is reduced.
[0017] In addition, in the case of obtaining a three-dimensional microcrystalline glass, it is usually formed after crystallization, but depending on the composition of the glass, there is a problem that the haze deteriorates and the transparency of the glass decreases due to heating during forming. On the other hand, in the method of performing crystallization after bending, there is a problem that deformation is easily caused and the transparency decreases due to the heat treatment for crystallization. Under these circumstances, it is difficult to obtain a three-dimensional microcrystalline glass suitable for protective glass with excellent transparency, strength and shape stability.
[0018] An object of the present invention is to provide three-dimensional shaped glass having excellent strength, transparency and shape stability and a method for producing the same.
[0019] Means used to solve problems
[0020] In view of the above problems, the present inventors have repeatedly conducted intensive studies on glass composition, etc., and as a result, have found three-dimensional shaped glass excellent in strength, transparency and shape stability and a method for producing the same, thereby completing the present invention.
[0021] The present invention provides a microcrystalline glass, which comprises a microcrystalline glass having an average curvature radius of 5.0×10 2 The smallest R shape and average curvature radius of 1.0×10 3 A three-dimensional glass-ceramic having a maximum R shape of more than mm and composed of a plurality of R shapes, wherein
[0022] The maximum value of the retardation measured by the following measurement method is 20 nm / mm or less, and
[0023] The haze value of the largest R shape when converted to a thickness of 0.8 mm is 1.0% or less.
[0024] (Measurement method)
[0025] Light of 543 nm wavelength was vertically irradiated to one or more points on each R-shaped arc, and the retardation was measured using a birefringence measuring device. However, when the angle between the tangent line of the curved surface at the center of the measurement sample and the tangent line of the measurement target surface was 90° or more, no measurement was performed.
[0026] The present invention relates to a chemically strengthened glass having a compressive stress layer on the surface and comprising a glass having an average curvature radius of 5.0×10 2 The smallest R shape and average curvature radius of 1.0×10 3 A three-dimensional chemically strengthened glass having a maximum R shape of mm or more and composed of a plurality of R shapes, wherein
[0027] The surface compressive stress value of the chemically strengthened glass is 500 MPa or more and the depth of the compressive stress layer is 80 μm or more.
[0028] The chemically strengthened glass is a microcrystalline glass containing crystals.
[0029] The maximum value of the retardation per 1 mm thickness measured by vertically irradiating the center of the smallest R shape with light having a wavelength of 543 nm is 20 nm / mm or less, and
[0030] The haze value of the largest R shape when converted to a thickness of 0.8 mm is 1.0% or less.
[0031] The present invention relates to a method for manufacturing a three-dimensional glass-ceramic, wherein the method for manufacturing a three-dimensional glass-ceramic comprises:
[0032] The amorphous glass is heated and bent to obtain a glass having an average curvature radius of 5.0×10 2 The smallest R shape and average curvature radius of 1.0×10 3 A process for forming a three-dimensional amorphous glass having a maximum R shape of more than mm and composed of a plurality of R shapes; and
[0033] a step of crystallizing the three-dimensional amorphous glass by heat treatment to obtain three-dimensional microcrystalline glass;
[0034] The amorphous glass contains, in terms of mass % based on oxides:
[0035] 58%~74% SiO2,
[0036] 5% to 30% Al2O3,
[0037] 1% to 14% Li2O,
[0038] 0~5% Na2O,
[0039] 0~2% K2O,
[0040] 0.5% to 12% in total of any one or more of SnO2 and ZrO2, and
[0041] 0~6% P2O5.
[0042] The present invention relates to a method for manufacturing a three-dimensional shaped chemically strengthened glass, wherein the method for manufacturing a three-dimensional shaped chemically strengthened glass comprises:
[0043] The amorphous glass is heated and bent to obtain a glass having an average curvature radius of 5.0×10 2 The smallest R shape and average curvature radius of 1.0×10 3 A process for forming amorphous glass in a three-dimensional shape composed of a plurality of R shapes with a maximum R shape of mm or more;
[0044] A step of crystallizing the three-dimensional amorphous glass by heat treatment to obtain three-dimensional microcrystalline glass; and
[0045] a step of chemically strengthening the three-dimensional glass-ceramics,
[0046] The amorphous glass contains, in terms of mass % based on oxides:
[0047] 58%~74% SiO2,
[0048] 5% to 30% Al2O3,
[0049] 1% to 14% Li2O,
[0050] 0~5% Na2O,
[0051] 0~2% K2O,
[0052] 0.5% to 12% in total of any one or more of SnO2 and ZrO2, and
[0053] 0~6% P2O5.
[0054] Effects of the Invention
[0055] The three-dimensional shaped glass according to the present invention comprises a plurality of glass sheets having an average curvature radius of 5.0×10 2 The smallest R shape and average curvature radius of 1.0×10 3 The three-dimensional shape is composed of a plurality of R shapes with a maximum R shape of 1.0 mm or more, wherein the maximum value of the retardation per 1 mm thickness measured by irradiating the above smallest R shape with light of a wavelength of 543 nm vertically is 20 nm / mm or less, thereby being not easy to break and having excellent strength and molding stability. In addition, the haze value of the above largest R shape when converted to a thickness of 0.8 mm is 1.0% or less, and the transparency is excellent.
[0056] According to the method for manufacturing three-dimensional shaped glass of the present invention, after the step of heating amorphous glass having a specific composition and bending it to form a three-dimensional shaped amorphous glass, a step of crystallizing by heat treatment is included, thereby reducing the delay generated during forming and improving the strength. In addition, the haze deterioration caused by heating during forming can be suppressed to achieve excellent transparency. BRIEF DESCRIPTION OF THE DRAWINGS
[0057] Figure 1 This is a perspective view showing an example of the shape of the three-dimensional shaped glass of the present invention.
[0058] Figure 2 1 is a diagram showing an example of the shape of the three-dimensional shaped glass of the present invention. Figure 2 (a) is the main view, Figure 2 (b) is a stereogram.
[0059] Figure 3 1 is a diagram showing an example of the shape of the three-dimensional shaped glass of the present invention. Figure 3 (a) is the main view, Figure 3 (b) is a stereogram.
[0060] Figure 4 This is a diagram showing an example of an X-ray diffraction pattern of glass-ceramics.
[0061] Figure 5This is a schematic diagram showing one embodiment of a method for producing three-dimensional shaped glass according to the present invention. DETAILED DESCRIPTION
[0062] In this specification, "to" indicating a numerical range is used to include the numerical values described before and after it as the lower limit and the upper limit. Unless otherwise specified, "to" is used in the following description in this specification with the same meaning as above.
[0063] In this specification, "amorphous glass" and "microcrystalline glass" are collectively referred to as "glass". In this specification, "amorphous glass" refers to glass in which no diffraction peak indicating crystals can be observed using the powder X-ray diffraction method. "Microcrystalline glass" refers to glass in which crystals are precipitated by heating "amorphous glass", and it contains crystals.
[0064] In the powder X-ray diffraction measurement, CuKα rays are used to measure 2θ in the range of 10° to 80°, and when a diffraction peak appears, the precipitated crystal is identified by, for example, a three-line method.
[0065] Hereinafter, "chemically strengthened glass" refers to glass subjected to a chemical strengthening treatment, and "glass for chemical strengthening" refers to glass before subjected to a chemical strengthening treatment.
[0066] In addition, "basic composition of chemically strengthened glass" refers to the glass composition of chemically strengthened glass. Except for the case of extreme ion exchange treatment, the glass composition of the part deeper than the depth of compressive stress layer (DOL) of the chemically strengthened glass is the basic composition of the chemically strengthened glass.
[0067] In this specification, unless otherwise specified, the glass composition is expressed in mass % based on oxides, and mass % is abbreviated as "%".
[0068] In this specification, "substantially not containing" means that the content is below the level of impurities contained in raw materials, etc., that is, not intentionally added. In this specification, when it is stated that a certain component is substantially not contained, the content of the component is, for example, less than 0.1%.
[0069] In this specification, "stress distribution" refers to a graph showing the value of compressive stress as a variable of the depth from the glass surface. In the stress distribution, tensile stress is expressed as negative compressive stress.
[0070] The "compressive stress value (CS)" or "surface compressive stress value (CS0)" can be measured by making a thin slice of the cross section of the glass and analyzing the thin slice sample using a birefringence imaging system. As a birefringence imaging system, there is, for example, the birefringence imaging system Abrio-IM manufactured by Tokyo Instruments Co., Ltd. In addition, the "compressive stress value (CS)" or "surface compressive stress value (CS0)" can also be measured using scattered light photoelasticity. In this method, CS can be measured by making light incident from the surface of the glass and analyzing the polarized light of the scattered light. As a stress measuring instrument using scattered light photoelasticity, there is, for example, the scattered light photoelasticity stress meter SLP-1000 manufactured by Orihara Manufacturing Co., Ltd.
[0071] In this specification, "compressive stress layer depth (DOL)" refers to the depth when the compressive stress value (CS) is zero. In this specification, "internal tensile stress (CT)" refers to the tensile stress value at a depth of 1 / 2 of the plate thickness t.
[0072] In this specification, "retardation" refers to a value converted to a thickness of 0.55 mm by irradiating light having a wavelength of 543 nm from a direction perpendicular to the main surface of the glass plate using a birefringence meter. Examples of the birefringence meter include WPA-100 and WPA-200 manufactured by Photonic Lattice.
[0073] In this specification, "light transmittance" refers to the average transmittance of visible light with a wavelength of 380nm to 780nm. In addition, "haze value" refers to the value obtained by measuring using C light source in accordance with JIS K3761:2000. "Haze value when converted to a thickness of 0.8mm" refers to the haze value obtained by measuring the thickness of the object to be measured when the thickness is not 0.8mm and the object is processed to a thickness of 0.8mm. Alternatively, "haze value when converted to a thickness of 0.8mm" refers to the haze value equivalent to the case of a thickness of 0.8mm, which is calculated based on the haze value measured at the original thickness and the haze value measured after processing to change the thickness.
[0074] In this specification, "thermal expansion coefficient" refers to the average thermal expansion coefficient in the range of 50°C to 500°C, measured at a heating rate of 10°C / min according to JIS R1618:2002 unless otherwise specified. In addition, "glass transition temperature" refers to a value obtained from the thermal expansion curve.
[0075] In this specification, "Vickers hardness" means the Vickers hardness (HV0.1) specified in JIS R1610:2003.
[0076] In addition, the “fracture toughness value” can be measured using a DCDC method (Actametall. mater. Vol. 43, pp. 3453-3458, 1995).
[0077] <Three-dimensional shape glass>
[0078] The three-dimensional shape glass of the present invention includes three-dimensional shape glass-ceramics and three-dimensional shape chemically strengthened glass. In the present invention, the "three-dimensional shape" refers to a shape having an average curvature radius of 5.0×10 2 The smallest R shape and average curvature radius of 1.0×10 3 The three-dimensional shape in the present invention includes any of a curved shape including a continuous curve, a shape curved in the longitudinal and transverse directions, and a shape having concavities and convexities on a plane.
[0079] Figure 1 , Figure 2 , Figure 3 These are diagrams showing an example of the three-dimensional shape glass of the present invention. These diagrams show a three-dimensional shape glass having a uniform thickness throughout, but the three-dimensional shape may also have a shape having portions with different thicknesses.
[0080] Figure 1 The three-dimensional shaped glass 100 has a peripheral portion 120 around a center portion 110 which is a substantially flat surface, includes a minimum R shape between the center portion 110 and the peripheral portion 120 , and includes a maximum R shape in the center portion 110 which is a substantially flat surface.
[0081] Figure 2 (a) and (b) represent glass of the following shapes: the glass includes a pair of minimum R shapes with an average curvature radius of R1 at both ends of the inner surface (inner surface), which are bent in a direction away from the outer surface toward the two ends, and includes a maximum R shape with an average curvature radius of R2 that is bent upward (in the figure).
[0082] Figure 3 (a) and (b) represent glass of the following shapes: the glass includes a pair of minimum R shapes with an average curvature radius of R1 at the two ends of the inner surface, which are bent in a direction away from the outer surface toward the two ends, and includes a maximum R shape with an average curvature radius of R2 that is bent downward (in the figure).
[0083] The mean curvature is a physical index value indicating the degree to which a surface deviates from a plane. The mathematical derivation of the mean curvature is well known and is omitted in this specification. In simple terms, the mean curvature of a surface is defined as the middle value between the maximum and minimum values of the curvature of a rotating body obtained by rotating the surface with the normal vector of the surface at a certain point on the surface as the center and rotating the surface. In addition, the mean curvature radius of the surface is defined as the reciprocal of the mean curvature.
[0084] The following specific examples are given: the average curvature of any point on the spherical surface of a sphere with a radius of R is 1 / R. In addition, at any point on the side of a cylinder with a radius of R at the bottom, the maximum curvature is 1 / R and the minimum curvature is 0, so the average curvature is 1 / 2R. Therefore, the value of the average curvature at a point on the surface is an important parameter for expressing the physical shape. The average curvature can be measured by any known method.
[0085] The average curvature radius R1 of the smallest R shape is 5.0×10 2 mm or less, preferably 1.0×10 2 mm or less, more preferably 5.0×10 1 The average radius of curvature R1 is preferably 1.0 mm or more, more preferably 2.5 mm or more, and further preferably 5.0 mm or more. The bending angle of the smallest R shape is preferably 1° or more, more preferably 10° or more, and further preferably 20° or more. In addition, the bending angle of the smallest R shape is preferably 89° or less, more preferably 80° or less, and further preferably 75° or less.
[0086] The average curvature radius R2 of the largest R shape is 1.0×10 3 mm or more, preferably 2.5×10 3 mm or more, more preferably 5.0×10 3 mm or more. In addition, the average curvature radius R2 is preferably 4.0×10 5 mm or less, more preferably 2.0×10 5 mm or less, more preferably 1.0×10 5 The maximum R-shaped bending angle is preferably in the range of greater than 0° to 10.0°, more preferably in the range of greater than 0° to 8.0°, and further preferably in the range of greater than 0° to 5.0°.
[0087] The stress remaining inside the three-dimensional shaped glass of the present invention can be evaluated using retardation as an index. For example, the refractive index difference (refractive index anisotropy) between the refractive index for a first linear polarized light of a specified wavelength and the refractive index for a second linear polarized light orthogonal to the first linear polarized light measured using a birefringence measuring device is set to Δn, and the thickness of the central portion of the present three-dimensional shaped glass is set to t [nm].
[0088] At this time, the level of residual stress can also be evaluated based on the measured delay Δn×t[nm]. In addition, the delay is not limited to the case where the actual thickness (t[nm]) of the center of the three-dimensional shape glass is directly used, and it can also be evaluated in the form of delay Δn×d[nm / mm] per 1mm thickness. In this case, it can be calculated using d=t[nm] / t[mm].
[0089] The maximum retardation value of the three-dimensional shaped glass of the present invention measured by the following measurement method is 20 nm / mm or less, preferably 18 nm / mm or less, and more preferably 16 nm / mm or less. The retardation value may be measured on at least one cross section.
[0090] (Measurement method)
[0091] Light of 543 nm wavelength was vertically irradiated to one or more points on each R-shaped arc, and the retardation was measured using a birefringence measuring device. However, when the angle between the tangent line of the curved surface at the center of the measurement sample and the tangent line of the measurement target surface was 90° or more, no measurement was performed.
[0092] The magnitude of the delay depends on the stress in the glass, and a small maximum value of the delay indicates a small stress difference in the glass. The three-dimensional shaped glass of the present invention is not easily broken by having a maximum value of the delay of 20 nm / mm or less, and has excellent strength and forming stability. There is no particular restriction on the lower limit of the maximum value of the delay, but it is usually 1 nm / mm or more.
[0093] The haze value of the three-dimensional shaped glass of the present invention when the largest R shape is converted to a thickness of 0.8 mm is 1.0% or less, preferably 0.8% or less, more preferably 0.5% or less, further preferably 0.4% or less, extremely preferably 0.3% or less, and most preferably 0.25% or less. By having the haze value of 1.0% or less, excellent transparency can be achieved, and it is suitable for the protective glass of the display part of a portable terminal or the like.
[0094] On the other hand, if the haze is difficult to reduce without reducing the crystallization rate, the haze value of the largest R shape converted to a thickness of 0.8 mm is preferably 0.05% or more, more preferably 0.08% or more, in order to improve mechanical strength and the like.
[0095] The light transmittance of the three-dimensional shape glass of the present invention when the largest R shape is converted to a thickness of 0.8 mm is preferably 85% or more, more preferably 87% or more, further preferably 88% or more, and particularly preferably 89% or more. When the light transmittance is 85% or more, it is easy to see the screen in the case of a protective glass used for a portable display. The higher the light transmittance, the more preferred, but it is usually 91% or less or 90% or less. 91% is the same transmittance as ordinary amorphous glass.
[0096] The three-dimensional shape glass of the present invention is a microcrystalline glass, so it has high strength compared with amorphous glass, and has a large Vickers hardness, so it is not easy to damage. For wear resistance, the Vickers hardness is preferably 700 or more, more preferably 740 or more, and more preferably 780 or more. On the other hand, when the Vickers hardness is too large, it is sometimes difficult to process, so the Vickers hardness is preferably 1100 or less, more preferably 1050 or less, and more preferably 1000 or less.
[0097] <Glass-ceramic>
[0098] The glass-ceramics of the present invention is included in the above-mentioned three-dimensional shaped glass and is a three-dimensional shaped glass-ceramics.
[0099] In order to suppress warping during chemical strengthening treatment, the Young's modulus of the glass-ceramics of the present invention is preferably 80 GPa or more, more preferably 85 GPa or more, further preferably 87 GPa or more, and particularly preferably 90 GPa or more. When the Young's modulus is too high, grinding and other processing become difficult, so in order to improve processability, the Young's modulus is preferably 130 GPa or less, more preferably 125 GPa or less, and further preferably 120 GPa or less.
[0100] The fracture toughness value of the glass-ceramics of the present invention is preferably 0.8 MPa·m 1 / 2 More preferably, 1 MPa·m 1 / 2 When the fracture toughness value is within the above range, fragments are less likely to fly when the tempered glass breaks.
[0101] The average thermal expansion coefficient of the glass-ceramics of the present invention in the range of 50°C to 500°C is preferably 30×10 -7 / °C or less, more preferably 25×10 -7 / °C or less, more preferably 20×10 -7 / °C or less, particularly preferably 15×10 -7 / ℃ or less. The average thermal expansion coefficient in the range of 50℃~500℃ is usually 10×10 -7 / ℃ or above.
[0102] The glass-ceramics of the present invention preferably contains crystals of lithium aluminosilicate. Glass-ceramics containing crystals of lithium aluminosilicate can obtain high strength because the precipitated crystals are also strengthened by chemical strengthening treatment.
[0103] In the case where the strength after chemical strengthening is to be further improved, the microcrystalline glass of the present invention is preferably a microcrystalline glass containing β-spodumene crystals. β-spodumene crystals are represented by LiAlSi2O6, which are lithium aluminum silicate crystals that show diffraction peaks at Bragg angles (2θ) of 25.55°±0.05°, 22.71°±0.05°, and 28.20°±0.05° in the X-ray diffraction spectrum.
[0104] exist Figure 4 Examples of X-ray diffraction patterns of glass-ceramics containing β-spodumene crystals and strengthened glass-ceramics (chemically strengthened glass) are shown in FIG. Figure 4 In the figure, the solid line is the X-ray diffraction pattern measured on the glass-ceramic plate before strengthening, and it is observed that Figure 4 The black circles in the figure show the diffraction lines of β-spodumene crystals. The dotted lines show the X-ray diffraction pattern of a chemically strengthened glass-ceramic (chemically strengthened glass) plate.
[0105] Compared with glass-ceramics containing other crystals, glass-ceramics containing β-spodumene crystals have a tendency to increase surface compressive stress value (CS0) by chemical strengthening. It is believed that since the crystal structure of β-spodumene crystals is dense, the compressive stress generated by the change in crystal structure when the ions in the precipitated crystals are replaced with larger ions by ion exchange treatment for chemical strengthening is large, and the effect of chemical strengthening becomes greater.
[0106] It is known that the crystal growth rate of β-spodumene crystals is fast. Therefore, the crystals contained in the microcrystalline glass containing β-spodumene crystals tend to grow larger, so in most cases, the transparency is low and the haze value is large. However, the microcrystalline glass of the present invention contains a large number of tiny crystals, has high transparency, and has a small haze value.
[0107] In order to improve the mechanical strength, the crystallization rate of the microcrystalline glass of the present invention is preferably 10% or more, more preferably 15% or more, further preferably 20% or more, and particularly preferably 25% or more. On the other hand, the crystallization rate is preferably 95% or less, more preferably 90% or less, and particularly preferably 85% or less. By making the crystallization rate 80% or less, it is possible to easily bend and shape it by heating while improving transparency.
[0108] The crystallinity ratio can be calculated from the X-ray diffraction intensity using the Rydberg method, which is described in the Crystal Analysis Handbook edited by the Crystal Analysis Handbook Editorial Committee of the Crystallographic Society of Japan (Kyoritsu Publishing, 1999, pp. 492-499).
[0109] The average particle size of the precipitated crystals of the glass-ceramics of the present invention is preferably 300 nm or less, more preferably 200 nm or less, and further preferably 150 nm or less. The average particle size of the precipitated crystals can be calculated from the powder X-ray diffraction intensity using the Riedbold method.
[0110] In terms of mass % based on oxides, the glass-ceramics of the present invention preferably contains 58% to 74% SiO2, 5% to 30% Al2O3, 1% to 14% Li2O, 0 to 5% Na2O and 0 to 2% K2O. In addition, it is more preferred to contain a total of 0.5% to 12% of any one or more of SnO2 and ZrO2 and 0 to 6% P2O5. In the above composition, it is further preferred to contain 2% to 14% Li2O. In addition, it is particularly preferred that Na2O+K2O is 1% to 5%.
[0111] In addition, the following microcrystalline glass is further preferred, which contains, in terms of mass % based on oxides, 58% to 70% SiO2, 15% to 30% Al2O3, 2% to 10% Li2O, 0 to 5% Na2O, 0 to 2% K2O, 0.5% to 6% SnO2, 0.5% to 6% ZrO2 and 0 to 6% P2O5, and the Na2O+K2O is 1% to 5%.
[0112] That is, the glass-ceramics of the present invention is preferably glass obtained by crystallizing the amorphous glass having the above composition.
[0113] <Chemically strengthened glass>
[0114] The three-dimensional shaped glass of the present invention is preferably a glass obtained by chemical strengthening. That is, the chemically strengthened glass of the present invention is included in the above-mentioned three-dimensional shaped glass and is a three-dimensional shaped chemically strengthened glass.
[0115] When the surface compressive stress value (CS0) of the chemically strengthened glass of the present invention is 500 MPa or more, it is not easy to break due to deformation such as warping, so it is preferred. The surface compressive stress value of the chemically strengthened glass of the present invention is more preferably 600 MPa or more, further preferably 800 MPa or more, and particularly preferably 1000 MPa or more.
[0116] The chemically strengthened glass of the present invention preferably has a compressive stress layer depth (DOL) of 80 μm or more because it is less likely to break even when scratches occur on the surface. The DOL is more preferably 90 μm or more, further preferably 100 μm or more, and particularly preferably 120 μm or more.
[0117] In addition, when the maximum depth when the compressive stress value reaches 50 MPa or more (hereinafter sometimes referred to as "50 MPa depth") is 80 μm or more, it is not easy to break even when dropped on a hard surface such as asphalt, so it is more preferable. The 50 MPa depth is more preferably 90 μm or more, and particularly preferably 100 μm or more.
[0118] When the internal tensile stress (CT) of the chemically strengthened glass of the present invention is 110 MPa or less, it is preferred because fragments are not easily scattered when the strengthened glass breaks. CT is more preferably 100 MPa or less, and further preferably 90 MPa or less. On the other hand, when CT is reduced, CS becomes smaller, and there is a tendency that it is difficult to obtain sufficient strength. Therefore, CT is preferably 50 MPa or more, more preferably 55 MPa or more, and further preferably 60 MPa or more.
[0119] The 4-point bending strength of the chemically strengthened glass of the present invention is preferably 900 MPa or more, more preferably 1000 MPa or more, and further preferably 1100 MPa or more. Here, the 4-point bending strength is measured using a test piece of 40 mm × 5 mm × 0.8 mm, under the conditions of a lower span of 30 mm, an upper span of 10 mm, and a crosshead speed of 0.5 mm / min. The average value of 10 test pieces is taken as the 4-point bending strength.
[0120] The light transmittance and haze value of the chemically strengthened glass of the present invention are substantially the same as those of the three-dimensional shaped glass before chemical strengthening. In addition, the chemically strengthened glass of the present invention preferably contains β-spodumene crystals like the three-dimensional shaped glass before chemical strengthening.
[0121] The Vickers hardness of the chemically strengthened glass of the present invention tends to be greater than that of the three-dimensional shape glass before chemical strengthening. The Vickers hardness of the chemically strengthened glass of the present invention is preferably 720 or more, more preferably 740 or more, further preferably 780 or more, and further preferably 800 or more. In addition, the Vickers hardness of the chemically strengthened glass of the present invention is usually 950 or less.
[0122] <Method for producing three-dimensional glass-ceramics>
[0123] The method for producing three-dimensionally shaped glass-ceramics of the present invention includes the following steps (1) and (2).
[0124] (1) a process of heating amorphous glass and bending it to obtain a three-dimensional amorphous glass;
[0125] (2) A step of crystallizing the three-dimensional amorphous glass by heat treatment to obtain a three-dimensional microcrystalline glass
[0126] Hereinafter, each step will be described.
[0127] (1) A process of placing amorphous glass on a forming mold and forming the amorphous glass into a three-dimensional shape by heating
[0128] Step (1) is a step of bending the amorphous glass into a curved shape to obtain a three-dimensional amorphous glass.
[0129] (Amorphous glass)
[0130] The glass composition of the amorphous glass is preferably the following composition: in terms of mass % based on oxides, the glass composition of the amorphous glass contains 58% to 74% SiO2, 5% to 30% Al2O3, 1% to 14% Li2O, 0 to 5% Na2O, 0 to 2% K2O, 0.5% to 12% in total of any one or more of SnO2 and ZrO2, and 0 to 6% P2O5. In the above composition, it is more preferred to contain 2% to 14% Li2O, and it is more preferred that Na2O+K2O is 1% to 5%.
[0131] In addition, the glass composition of the amorphous glass further preferably contains 58% to 70% SiO2, 15% to 30% Al2O3, 2% to 10% Li2O, 0 to 5% Na2O, 0 to 2% K2O, 0.5% to 6% SnO2, 0.5% to 6% ZrO2, and 0 to 6% P2O5, calculated on a mass basis based on oxides, and Na2O+K2O is 1% to 5%.
[0132] These glass compositions are described below.
[0133] SiO2 is a component that forms a network structure of glass. In addition, SiO2 is a component that improves chemical durability, and is a constituent of lithium aluminum silicate crystals, and is also a constituent of lithium silicate crystals. The content of SiO2 is preferably 58% or more, more preferably 60% or more, and further preferably 64% or more. On the other hand, when the content of SiO2 is too much, the solubility is significantly reduced, so the content of SiO2 is preferably 74% or less, more preferably 70% or less, further preferably 68% or less, and particularly preferably 66% or less.
[0134] Al2O3 is an essential component that is effective in increasing the compressive stress generated by chemical strengthening. In addition, Al2O3 is a constituent of lithium aluminum silicate crystals. The content of Al2O3 is preferably 5% or more, and in the case of wanting to precipitate β-spodumene crystals, the content of Al2O3 is more preferably 15% or more. The content of Al2O3 is further preferably 20% or more. On the other hand, when the content of Al2O3 is too much, the devitrification temperature of the glass becomes higher. The content of Al2O3 is preferably 30% or less, and more preferably 25% or less.
[0135] Li2O is a component that forms compressive stress through ion exchange and is an essential component of lithium aluminum silicate crystals. The content of Li2O is preferably 1% or more, more preferably 2% or more, and further preferably 4% or more. On the other hand, the content of Li2O is preferably 14% or less, and in the case of precipitating β-spodumene crystals, it is more preferably 10% or less, further preferably 8% or less, and particularly preferably 6% or less.
[0136] When a glass-ceramic containing β-spodumene crystals is prepared, it is preferred that the content ratio of Li2O to Al2O3 is 0.3 or less because the transparency is high. This is believed to be because crystallization proceeds rapidly during heat treatment, thereby increasing the crystal size.
[0137] Na2O is a component that improves the melting property of glass. Na2O is not essential, but its content is preferably 0.5% or more, more preferably 1% or more. When Na2O is too much, lithium aluminum silicate crystals are not easily precipitated or chemical strengthening properties are reduced, so the content of Na2O is preferably 5% or less, more preferably 4% or less, and further preferably 3% or less.
[0138] K2O, like Na2O, is a component that lowers the melting temperature of glass and may be contained. When K2O is contained, the content of K2O is preferably 0.5% or more, more preferably 1% or more. In addition, the total content of Na2O and K2O (Na2O+K2O) is preferably 1% or more, more preferably 2% or more.
[0139] When K2O is excessive, lithium aluminum silicate crystals are not easily precipitated, so the content is preferably 2% or less. In addition, when the total content of Na2O and K2O (Na2O+K2O) is excessive, the promotion of crystallization is hindered during heat treatment, and the transparency may be reduced. In order to improve transparency, the total content is preferably 5% or less, more preferably 4% or less, and further preferably 3% or less.
[0140] ZrO2 and SnO2 are not essential, but ZrO2 and SnO2 are components that constitute the crystal nucleus during the crystallization process, so it is preferred to contain more than one of them. In order to generate the crystal nucleus, the total content of SnO2 and ZrO2, SnO2+ZrO2, is preferably 0.5% or more, and more preferably 1% or more. In order to form a large number of crystal nuclei and improve transparency, the total content is more preferably 3% or more, further preferably 4% or more, further preferably 5% or more, particularly preferably 6% or more, and most preferably 7% or more. In addition, in order to prevent defects caused by unmelted materials from occurring in the glass, the total content is preferably 12% or less, more preferably 10% or less, further preferably 9% or less, and particularly preferably 8% or less.
[0141] In order to precipitate β-spodumene crystals, it is preferred to contain 0.5% or more of SnO2. The content of SnO2 is more preferably 1% or more, and further preferably 1.5% or more. When the content of SnO2 is 6% or less, defects caused by unmelted materials are less likely to occur in the glass, so it is preferred. The content of SnO2 is more preferably 5% or less, and further preferably 4% or less.
[0142] SnO2 is also a component that improves solarization resistance. In order to suppress solarization, the content of SnO2 is preferably 1% or more, and more preferably 1.5% or more.
[0143] Generally, TiO2 and ZrO2 are known as crystal nucleus forming components of microcrystalline glass. According to the research of the inventors, in this composition, the effect of ZrO2 is higher than that of TiO2. In addition, by adding SnO2, the transparency of microcrystalline glass becomes higher.
[0144] The content of ZrO2 is preferably 0.5% or more, more preferably 1% or more. On the other hand, when the content of ZrO2 is 6% or less, devitrification is not easy during melting, and the quality reduction of chemically strengthened glass can be suppressed. The content of ZrO2 is preferably 6% or less, more preferably 5% or less, and further preferably 4% or less.
[0145] When SnO2 and ZrO2 are contained simultaneously, in order to improve transparency, the ratio of the amount of SnO2 to their total amount, SnO2 / (SnO2+ZrO2), is preferably greater than 0.3, more preferably greater than 0.35, and further preferably greater than 0.45.
[0146] In order to improve the strength, SnO2 / (SnO2+ZrO2) is preferably 0.7 or less, more preferably 0.65 or less, and further preferably 0.6 or less.
[0147] TiO2 is a crystal nucleus-forming component of microcrystalline glass, so TiO2 may be contained. When TiO2 is contained, the content of TiO2 is preferably 0.1% or more, more preferably 0.15% or more, and further preferably 0.2% or more. On the other hand, when the content of TiO2 is 5% or less, it is not easy to lose clarity during melting, and the quality reduction of chemically strengthened glass can be suppressed, so the content of TiO2 is preferably 5% or less. The content of TiO2 is more preferably 3% or less, and further preferably 1.5% or less.
[0148] In addition, when Fe2O3 is contained in the glass, when TiO2 is contained in the glass, a complex called ilmenite complex is formed, which is easy to produce yellow or brown coloration. Fe2O3 is usually contained in the glass as an impurity, so in order to prevent coloration, the content of TiO2 is preferably 1% or less, more preferably 0.5% or less, further preferably 0.25% or less, and particularly preferably substantially free of it.
[0149] P2O5 is not essential, but P2O5 has the effect of promoting phase separation of glass and promoting crystallization, so P2O5 may be contained. When P2O5 is contained, the content of P2O5 is preferably 0.1% or more, more preferably 0.5% or more, further preferably 1% or more, and particularly preferably 2% or more.
[0150] On the other hand, when the content of P2O5 is too high, the crushability of the chemically strengthened glass deteriorates, and the acid resistance is significantly reduced. The content of P2O5 is preferably 6% or less, more preferably 5% or less, further preferably 4% or less, particularly preferably 3% or less, and most preferably 2% or less. In order to further improve the acid resistance, it is preferred that P2O5 is substantially not contained.
[0151] B2O3 is a component that improves the chipping resistance of chemically strengthened glass or chemically strengthened glass and improves the meltability, and B2O3 may be contained. B2O3 is not essential, but when B2O3 is contained, in order to improve the meltability, the content of B2O3 is preferably 0.5% or more, more preferably 1% or more, and further preferably 2% or more.
[0152] On the other hand, when the content of B2O3 is greater than 5%, ribs are generated during melting, and the quality of the chemically strengthened glass is easily reduced, so the content of B2O3 is preferably 5% or less. The content of B2O3 is more preferably 4% or less, further preferably 3% or less, and particularly preferably 1% or less. In order to improve acid resistance, it is preferred that substantially no B2O3 is contained.
[0153] MgO is a component that increases the compressive stress generated by chemical strengthening. It can be contained to suppress the scattering of fragments when the strengthened glass breaks. When MgO is contained, the content of MgO is preferably 0.5% or more, more preferably 1% or more. On the other hand, in order to suppress devitrification during melting, the content of MgO is preferably 5% or less, more preferably 4% or less, and further preferably 3% or less.
[0154] CaO is a component that improves the meltability of glass. CaO may be contained in order to prevent devitrification during melting and to improve meltability while suppressing an increase in the thermal expansion coefficient. When CaO is contained, the content of CaO is preferably 0.5% or more, more preferably 1% or more. On the other hand, in order to improve ion exchange properties, the content of CaO is preferably 4% or less, more preferably 3% or less, and particularly preferably 2% or less.
[0155] SrO is a component that improves the solubility of glass. SrO can also be contained because it can increase the refractive index of glass and make the refractive index of the residual glass phase after crystallization close to the refractive index of the precipitated crystals, thereby increasing the transmittance of the microcrystalline glass.
[0156] When SrO is contained, the content of SrO is preferably 0.1% or more, more preferably 0.5% or more, and further preferably 1% or more. On the other hand, when the content of SrO is too high, the ion exchange rate decreases, so from this point of view, the content of SrO is preferably 3% or less, more preferably 2.5% or less, further preferably 2% or less, and particularly preferably 1% or less.
[0157] BaO is a component that improves the solubility of glass. BaO may also be contained because it increases the refractive index of glass and makes the refractive index of the residual glass phase after crystallization close to that of the lithium aluminosilicate crystal phase, thereby increasing the transmittance of the microcrystalline glass.
[0158] When BaO is contained, the content of BaO is preferably 0.1% or more, more preferably 0.5% or more, and further preferably 1% or more. On the other hand, when the content of BaO is too high, the ion exchange rate decreases, so from this point of view, the content of BaO is preferably 3% or less, more preferably 2.5% or less, further preferably 2% or less, and particularly preferably 1% or less.
[0159] ZnO is a component that reduces the thermal expansion coefficient of glass and increases chemical durability. In addition, ZnO increases the refractive index of glass, and increases the transmittance of microcrystalline glass by making the refractive index of the residual glass phase after crystallization close to the refractive index of the lithium aluminum silicate crystal phase, so ZnO can be contained.
[0160] When ZnO is contained, the content of ZnO is preferably 0.5% or more, more preferably 1% or more, further preferably 1.5% or more, and particularly preferably 2% or more. On the other hand, in order to suppress devitrification during melting, the content of ZnO is preferably 4% or less, more preferably 3% or less, and further preferably 2% or less.
[0161] Y2O3, La2O3, Nb2O5 and Ta2O5 all have the effect of suppressing the scattering of fragments when the glass breaks. In order to increase the refractive index, Y2O3, La2O3, Nb2O5 and Ta2O5 can be contained. When these components are contained, the total content of Y2O3, La2O3 and Nb2O5 (Y2O3+La2O3+Nb2O5) is preferably 0.5% or more, more preferably 1% or more, further preferably 1.5% or more, and particularly preferably 2% or more. In addition, in order to make the glass less likely to lose transparency during melting, the content of Y2O3+La2O3+Nb2O5 is preferably 4% or less, more preferably 3% or less, further preferably 2% or less, and particularly preferably 1% or less.
[0162] The total content of Y2O3, La2O3, Nb2O5 and Ta2O5 (Y2O3+La2O3+Nb2O5+Ta2O5) is preferably 0.5% or more, more preferably 1% or more, further preferably 1.5% or more, and particularly preferably 2% or more. In addition, in order to prevent the glass from losing transparency during melting, Y2O3+La2O3+Nb2O5+Ta2O5 is preferably 4% or less, more preferably 3% or less, further preferably 2% or less, and particularly preferably 1% or less.
[0163] CeO2 has the effect of oxidizing glass. When a large amount of SnO2 is contained, coloring is sometimes suppressed by suppressing SnO2 from being reduced to SnO as a coloring component, so CeO2 may be contained. When CeO2 is contained, the content of CeO2 is preferably 0.03% or more, more preferably 0.05% or more, and further preferably 0.07% or more. When CeO2 is used as an oxidant, when the content of CeO2 is too much, the glass is easily colored. Therefore, in order to improve transparency, the content of CeO2 is preferably 1.5% or less, and more preferably 1.0% or less.
[0164] In addition, coloring components can be added within a range that does not hinder the desired chemical strengthening characteristics. As coloring components, for example, Co3O4, MnO2, Fe2O3, NiO, CuO, Cr2O3, V2O5, Bi2O3, SeO2, Er2O3, and Nd2O3 can be listed as appropriate components. The content of the coloring components is preferably in a range of 1% or less in total. In the case of further improving the light transmittance of the glass, it is preferably substantially free of these components.
[0165] In addition, SO3, chloride, fluoride, etc. may be appropriately contained as a clarifier during glass melting, etc. Preferably, As2O3 is not contained. When Sb2O3 is contained, the content of Sb2O3 is preferably 0.3% or less, more preferably 0.1% or less, and most preferably, no Sb2O3 is contained.
[0166] When the average thermal expansion coefficient is large, strain and cracking are likely to occur during cooling. Therefore, the average thermal expansion coefficient of amorphous glass in the range of 50°C to 500°C is preferably 100×10 -7 / °C or less, more preferably 80×10 -7 / °C or less, more preferably 60×10 -7 / ℃ or less. When the average thermal expansion coefficient of amorphous glass in the range of 50℃~500℃ is small, a thermal expansion difference between the mold and the amorphous glass occurs during molding, and the desired shape cannot be formed. Therefore, the average thermal expansion coefficient of amorphous glass in the range of 50℃~500℃ is preferably 10×10 -7 / ℃ or more, more preferably 30×10 -7 / ℃ or more, more preferably 40×10 -7 / ℃ or above.
[0167] When the thermal expansion difference between the mold material and the glass for bending forming described later is large, it is necessary to design the mold in consideration of the correction rate according to the target shape. By keeping the average thermal expansion coefficient of amorphous glass within the above range, when carbon is used as the mold material for bending forming, the thermal expansion difference between the glass and the mold can be reduced, and it is not necessary to design the mold by calculating the correction rate according to the target shape, which can improve productivity.
[0168] Amorphous glass can be produced, for example, by the method shown below. It should be noted that the method shown below is an example of the case of producing a plate-shaped amorphous glass.
[0169] Glass raw materials are mixed to obtain glass of preferred composition, and heated and melted in a glass melting furnace. Then, the molten glass is homogenized by bubbling, stirring, adding clarifiers, etc., and formed into a glass plate of a specified thickness by a known forming method, and then slowly cooled. Alternatively, it can also be formed into a plate by the following method: the molten glass is formed into a block, slowly cooled, and then cut.
[0170] As a method for manufacturing flat glass, for example, a float process, a press process, a fusion process, and a down-draw process can be used. In particular, when manufacturing a large glass plate, the float process is preferred. In addition, continuous forming methods other than the float process, such as the fusion process and the down-draw process, are also preferred.
[0171] (Bending)
[0172] Bending is a process of heating glass to form it into a curved shape and then rapidly cooling it from a high temperature without crystallizing it. Examples of bending methods include existing bending methods such as self-weight forming, vacuum forming, and press forming, and any method can be selected. In addition, two or more bending methods can be used in combination.
[0173] The self-weight forming method is a method in which a glass sheet is placed on a forming mold, the glass sheet is heated, and gravity is used to make the glass sheet fit into the forming mold, thereby bending the glass sheet into a predetermined shape.
[0174] The vacuum forming method is a method in which a glass sheet is placed on a forming mold, the periphery of the glass sheet is sealed, and then the space between the forming mold and the glass sheet is decompressed, and a differential pressure is applied to the front and back surfaces of the glass sheet to perform bending forming. At this time, the upper surface side of the glass sheet may be pressurized as an auxiliary.
[0175] Press forming is a method of placing a glass sheet between forming dies (a lower die and an upper die), heating the glass sheet, and applying a press load between the upper and lower forming dies to bend the glass sheet into a predetermined shape.
[0176] In either method, force is applied to the glass while it is heated to cause it to deform.
[0177] When the bending forming temperature (hereinafter also referred to as the hot bending temperature) is low, it is impossible to form into a desired shape, so the bending forming temperature is preferably 500°C or higher, more preferably 600°C or higher, further preferably 700°C or higher, and most preferably 750°C or higher. When the bending forming temperature is high, it is preferably 1100°C or lower, more preferably 1050°C or lower, and most preferably 900°C or lower because it does not exceed the upper temperature limit of the forming machine.
[0178] When the bending viscosity (balanced viscosity during bending) is low, it is not possible to form the desired shape. Therefore, the bending viscosity is preferably 10 8 Pa·s or more, more preferably 10 9 Pa·s or more, most preferably 10 10 Pa·s or more. Since it is difficult to maintain the desired shape when the bending viscosity is high, the bending viscosity is preferably 10 13 Pa·s or less, more preferably 10 12 Pa·s or less, most preferably 10 11.5 Pa·s or less.
[0179] When the crystallization temperature is close to the thermal bending temperature, crystal nucleation and crystal growth occur, so the difference between the crystallization temperature and the thermal bending temperature is preferably 5°C or more, more preferably 10°C or more, and further preferably 15°C or more. In order to suppress the decrease in transmittance caused by bending, the difference between the highest temperature of the crystallization treatment and the thermal bending temperature is preferably 200°C or less, more preferably 150°C or less, further preferably 130°C or less, and particularly preferably 100°C or less.
[0180] When nucleation is to be promoted during thermal bending, the difference between the nucleation temperature and the thermal bending temperature is preferably 10° C. or less. On the other hand, nucleation is preferably performed during crystallization treatment in terms of process control, and in this case, the temperature difference is preferably set to 10° C. or more.
[0181] When the thermal bending temperature is higher than the crystallization temperature, the transmittance may decrease due to bending. The transmittance decrease due to bending is preferably 3% or less, more preferably 2% or less, further preferably 1.5% or less, and particularly preferably 1% or less.
[0182] In order to maintain high transparency of the final glass, it is advantageous to have a high light transmittance before bending, and the light transmittance converted to a thickness of 0.8 mm is preferably 85% or more, more preferably 87% or more, and particularly preferably 89% or more.
[0183] The absolute value of the difference between the average thermal expansion coefficient of the amorphous glass in the range of 50°C to 500°C and the average thermal expansion coefficient of the mold material used in the bending forming in the range of 50°C to 500°C is preferably 150×10 -7 / °C or less, more preferably 100×10 -7 / °C or less, more preferably 50×10 -7 / ℃ or less, most preferably 30×10 -7 / ℃ below.
[0184] When the thermal expansion difference between the mold used in bending and the glass is large, the demolding property of the glass is poor. Therefore, the mold design needs to consider the correction rate calculated from the difference between the expansion rate of the glass and the expansion rate of the mold material, which reduces productivity. The absolute value of the above difference is 150×10 -7 / °C or less, the thermal expansion difference between the mold used in bending and the glass can be reduced, and there is no need to design the mold according to the target shape, which can improve productivity.
[0185] The average thermal expansion coefficient of the amorphous glass in the range of 50°C to 500°C in the present invention is close to that of carbon, so it is preferred to use a carbon mold made of carbon for bending. Thus, even without significant corrections, stress differences during forming can be suppressed, strength can be improved, and excellent dimensional stability and forming accuracy can be achieved.
[0186] In the present invention, when the average thermal expansion coefficient of the amorphous glass in the range of 50°C to 500°C is large, it is difficult to obtain a desired shape, so it is preferably 170×10 -7 / °C or less, more preferably 160×10 -7 / °C or less, more preferably 150×10 -7 / °C or less. In addition, when a carbon mold is used, the average thermal expansion coefficient is particularly preferably 60×10 -7 / °C or less. When the thermal expansion coefficient is low, the demolding property from the mold deteriorates, so it is preferably 20×10 -7 / ℃ or more, more preferably 30×10 -7 / ℃ or more, more preferably 40×10 -7 / ℃ or above.
[0187] From the viewpoint of suppressing crystal growth during molding, the difference between the glass transition temperature of the amorphous glass in the present invention and the highest temperature of the crystallization treatment is preferably 10° C. or more, more preferably 20° C. or more, and even more preferably 30° C. or more.
[0188] (2) A step of crystallizing the three-dimensional amorphous glass by heat treatment to obtain a three-dimensional microcrystalline glass
[0189] Step (2) is a step of obtaining three-dimensionally shaped microcrystalline glass by heat-treating the three-dimensionally shaped amorphous glass obtained in step (1).
[0190] The heat treatment in step (2) is preferably a two-step heat treatment: heating from room temperature to a first treatment temperature and maintaining the temperature for a certain period of time, and then maintaining the temperature at a second treatment temperature higher than the first treatment temperature for a certain period of time.
[0191] In the case of a two-step heat treatment, the first treatment temperature is preferably a temperature range in which the nucleation rate increases for the glass composition, and the second treatment temperature is preferably a temperature range in which the crystal growth rate increases for the glass composition. In addition, regarding the holding time at the first treatment temperature, it is preferably held for a long time so that a sufficient number of crystal nuclei are generated. By generating a large number of crystal nuclei, the size of each crystal becomes smaller, thereby obtaining a microcrystalline glass with high transparency.
[0192] The first treatment temperature is, for example, 550° C. to 800° C., and the second treatment temperature is, for example, 850° C. to 1000° C. The first treatment temperature is maintained for 2 hours to 10 hours, and then the second treatment temperature is maintained for 2 hours to 10 hours.
[0193] The three-dimensional glass-ceramics obtained by the above steps is ground and polished as needed. When the glass-ceramics plate is cut into a specified shape and size or chamfered, it is preferred to cut and chamfer before chemical strengthening treatment, because a compressive stress layer is also formed on the end face by the subsequent chemical strengthening treatment.
[0194] <Method for producing three-dimensional chemically strengthened glass>
[0195] The method for producing a three-dimensionally shaped chemically strengthened glass of the present invention includes the following steps (1) to (3).
[0196] (1) a process of heating amorphous glass and bending it to obtain a three-dimensional amorphous glass;
[0197] (2) a step of crystallizing the three-dimensional amorphous glass by heat treatment to obtain three-dimensional microcrystalline glass;
[0198] (3) A step of chemically strengthening the three-dimensionally shaped glass-ceramics obtained in step (2).
[0199] Steps (1) and (2) are the same as the steps (1) and (2) described in the <Method for Producing Three-Dimensional Shaped Glass-Ceramics>. Next, step (3) will be described.
[0200] Chemical strengthening treatment is a treatment in which metal ions with a small ionic radius (typically Na ions or Li ions) in the glass are replaced with metal ions with a large ionic radius (typically Na ions or K ions for Li ions, and K ions for Na ions) by bringing the glass into contact with the metal salt, etc., using methods such as immersing the glass in a molten solution of a metal salt (e.g., potassium nitrate) containing metal ions with a large ionic radius (typically Na ions or K ions for Li ions).
[0201] In order to speed up the chemical strengthening treatment, it is preferred to use "Li-Na exchange" in which Li ions in the glass are exchanged with Na ions. In addition, in order to form a large compressive stress by ion exchange, it is preferred to use "Na-K exchange" in which Na ions in the glass are exchanged with K ions.
[0202] As the molten salt for chemical strengthening treatment, nitrates, sulfates, carbonates, chlorides, etc. can be cited. Among them, as nitrates, for example, lithium nitrate, sodium nitrate, potassium nitrate, cesium nitrate, silver nitrate, etc. can be cited. As sulfates, for example, lithium sulfate, sodium sulfate, potassium sulfate, cesium sulfate, silver sulfate, etc. can be cited. As carbonates, for example, lithium carbonate, sodium carbonate, potassium carbonate, etc. can be cited. As chlorides, for example, lithium chloride, sodium chloride, potassium chloride, cesium chloride, silver chloride, etc. can be cited. These molten salts can be used alone or in combination.
[0203] Regarding the treatment conditions of the chemical strengthening treatment, the time, temperature, etc. can be appropriately selected in consideration of the glass composition, the type of molten salt, etc.
[0204] The chemically strengthened glass of the present invention is preferably obtained by, for example, the following two-step chemical strengthening treatment.
[0205] First, as the first step of chemical strengthening treatment, the three-dimensionally shaped microcrystalline glass is immersed in a metal salt containing Na ions (e.g., sodium nitrate) at about 350°C to about 500°C for about 0.1 hour to about 10 hours. As a result, ion exchange between the Li ions in the microcrystalline glass and the Na ions in the metal salt occurs, and for example, a compressive stress layer having a surface compressive stress value (CS0) of more than 200 MPa and a compressive stress layer depth of more than 80 μm can be formed. On the other hand, when the surface compressive stress value (CS0) is greater than 1000 MPa, it is difficult to increase the DOL while maintaining a low CT. The surface compressive stress value is preferably less than 900 MPa, more preferably less than 700 MPa, and further preferably less than 600 MPa.
[0206] Next, as a second step chemical strengthening treatment, the substrate is immersed in a metal salt containing K ions (e.g., potassium nitrate) at about 350° C. to about 500° C. for about 0.1 hour to about 10 hours. As a result, a large compressive stress is generated in a portion of the compressive stress layer formed by the previous treatment, for example, within a depth of about 10 μm.
[0207] According to such a two-step treatment, it is easy to obtain a preferred stress distribution with a surface compressive stress value (CS0) of 600 MPa or more.
[0208] Alternatively, the sample may be first immersed in a metal salt containing Na ions, then maintained in the atmosphere at 350°C to 500°C for 1 to 5 hours, and then immersed in a metal salt containing K ions. The holding temperature is preferably 325°C or higher, more preferably 340°C or higher. In addition, the holding temperature is preferably 475°C or lower, more preferably 460°C or lower.
[0209] By maintaining the glass at a high temperature in the atmosphere, Na ions introduced into the interior of the glass from the metal salt by the initial treatment are thermally diffused in the glass, thereby forming a more preferable stress distribution.
[0210] Alternatively, instead of maintaining in the atmosphere, the sample may be first immersed in a metal salt containing Na ions and then immersed in a metal salt containing Na ions and Li ions (e.g., a mixed salt of sodium nitrate and lithium nitrate) at a temperature in the range of 350°C to 500°C for 0.1 to 20 hours.
[0211] By immersing the glass in a metal salt containing Na ions and Li ions, ion exchange between Na ions in the glass and Li ions in the metal salt occurs, thereby forming a more preferred stress distribution, thereby being able to improve the pitch drop strength.
[0212] In the case of such a two-step or three-step strengthening treatment, from the viewpoint of production efficiency, the total treatment time is preferably 10 hours or less, more preferably 5 hours or less, and further preferably 3 hours or less. On the other hand, in order to obtain the desired stress distribution, the total treatment time requires more than 0.5 hours. The treatment time is more preferably more than 1 hour.
[0213] The three-dimensional shaped glass of the present invention is particularly useful as a protective glass used in display devices such as mobile phones and smart phones. In addition, it is also useful as a protective glass for display devices such as televisions, personal computers, touch panels, etc. that are not intended to be carried. It is also useful as a protective glass for interior decoration of automobiles, airplanes, etc.
[0214] Example
[0215] The present invention will be described below by way of examples, but the present invention is not limited thereto. In the table, blank columns indicate that no measurement was performed.
[0216] [Evaluation method]
[0217] (Glass transition temperature)
[0218] The glass transition temperature was measured using a thermal dilatometer (manufactured by Bruker AXS, TD5000SA).
[0219] (Delay)
[0220] Light having a wavelength of 543 nm was irradiated onto the glass, and the retardation value was measured at one or more locations on the arc of each R shape using a birefringence measuring device (WPA-100 manufactured by Photonic Lattice Corporation).
[0221] (Haze value)
[0222] The haze value of the largest R shape was measured using a haze meter (HZ-2, manufactured by Suga Test Instruments Co., Ltd.) in accordance with JIS K3761:2000.
[0223] (Coefficient of thermal expansion)
[0224] A thermal expansion curve was obtained by using a thermal dilatometer (manufactured by Bruker AXS, TD5000SA) with a heating rate of 10°C / min. In addition, the average linear thermal expansion coefficient (unit: ×10 -7 / ℃].
[0225] (Precipitation crystals)
[0226] Powder X-ray diffraction was measured under the following conditions to identify the precipitated crystals (main crystals).
[0227] Measurement device: SmartLab manufactured by Rigaku Corporation
[0228] Use X-ray: CuKα ray
[0229] Measuring range: 2θ = 10° to 80°
[0230] Speed: 10° / min
[0231] Step distance: 0.02°
[0232] (Average radius of curvature)
[0233] The average curvature radius was determined by using a three-dimensional measuring machine ATOS (model: ATOS Triple Scan III) manufactured by gom. The height coordinates of the sample surface relative to the cross-sectional direction were first measured at 0.1 mm intervals. The least squares method was then used to find the general formula of an approximate circle, and finally the average curvature radius was calculated.
[0234] [Manufacture of glass]
[0235] <Reference Example 1>
[0236] Glass raw materials were prepared to obtain 800 g of each of the glasses of compositions A to I shown in Table 1 in terms of mass % based on oxides, placed in a platinum crucible, and melted in an electric furnace at 1400°C to 1700°C for 5 hours. The degassed and homogenized molten glass was poured into a mold, kept at a temperature about 30°C higher than the glass transition temperature for 1 hour, and then cooled to room temperature at a cooling rate of 0.5°C / min to obtain a glass block. A glass plate with a thickness of 0.55 mm and a test piece for evaluating glass properties were obtained from the obtained glass block. The surface of the glass plate was mirror finished.
[0237] Table 1 shows the results of measuring the glass transition temperature and thermal expansion coefficient of the obtained glass plate.
[0238] Table 1
[0239]
[0240] Compositions B to I are examples of compositions suitable for the present invention. When they are heat treated, microcrystalline glass containing β-spodumene crystals can be obtained. The thermal expansion coefficients of compositions B to D, F, and G are within 40×10 -7 / ℃~60×10 -7 / °C range, when carbon is used as the mold material for bending, the thermal expansion difference between the glass and the mold can be reduced, and there is no need to design the mold based on target shape calculations, thereby improving productivity.
[0241] <Example 1>
[0242] A schematic diagram of one embodiment of the method for producing three-dimensional shaped glass of the present invention is shown in Figure 5 For the glass plate 13 of composition A (80 mm × 50 mm, R-shaped corner glass plate), C-chamfering was performed in the range of 0.2 mm from the glass end face. Here, "R-shaped corner" means that when the preform is viewed from directly above, the four corners are R-shaped. Chamfering was performed using a No. 600 grindstone (manufactured by TOKYO DIA) to make the surface roughness of the end face (arithmetic mean surface roughness of the chamfered portion) 450 nm.
[0243] A carbon die 11 and a punch 12 designed to be able to form a curved surface with a curvature radius of 6.0 mm and a bending depth of 4.0 mm were prepared, and a chamfered glass plate 13 was placed near the center of the glass contact surface of the die 11 .
[0244] The glass sheet 13 is preheated, deformed, and cooled while the female mold 11 and the male mold 12 on which the glass sheet 13 is placed are fixed to the lower shaft and the upper shaft of a forming device (Glass element forming device: GMP-315V manufactured by Toshiba Machine Co., Ltd.).
[0245] The preheating process takes 15 minutes to raise the temperature from room temperature to 600° C. At 600° C., the equilibrium viscosity of the glass plate 13 is about 10 13 Pa·s. Next, the temperature was raised from 600°C to 645°C over 5 minutes. The equilibrium viscosity of the glass plate 13 at 645°C was about 10 11.5 Pa·s.
[0246] The equilibrium viscosity of the central portion of the glass plate 13 is maintained at 10 11 Pa·s~10 12 The male mold 12 was moved downward in the range of 0.5 Pa·s (temperature was maintained in the range of 640°C to 650°C) and pressed against the female mold 11 for 3 minutes at a maximum of 2000 N. During this time, nitrogen gas was blown in at 20 L / min from a through hole (not shown) provided in the male mold 12 to uniformly shape the glass sheet 14.
[0247] Then, the glass plate was slowly cooled to 480° C. over 20 minutes. The equilibrium viscosity of the glass plate at 480° C. is about 10 21 Next, the punch 12 was raised at 2 mm / sec and retracted, and the glass plate 14 was naturally cooled to room temperature.
[0248] At room temperature, the average curvature radius of the smallest R shape of the glass plate 14 is 6.0 mm, the bending depth is 4.0 mm, and the average curvature radius of the largest R shape is 3.8×10 3The largest R shape is contained in the portion where the inner surface and the outer surface of the glass plate 14 are substantially parallel.
[0249] The surface of the glass plate 14 having the smallest R shape was irradiated with light having a wavelength of 543 nm vertically, and the retardation was measured. The maximum retardation value was 22 nm / mm.
[0250] <Example 2>
[0251] The glass plate 13 of composition B was chamfered in the same manner as in Example 1. The glass plate 13 was bent in the same manner as in Example 1 to obtain an R-shaped shape with an average curvature radius of 6.0 mm and a bending depth of 4.0 mm, and an R-shaped shape with an average curvature radius of 3.8×10 3 The largest R shape is contained in the portion where the inner surface and the outer surface of the glass plate 14 are substantially parallel.
[0252] The obtained glass plate 14 was placed on the male mold 12 and then kept at 750° C. for 4 hours and then at 900° C. for 4 hours, thereby crystallizing to obtain a three-dimensionally shaped microcrystalline glass 15 .
[0253] The maximum R-shape retardation of the obtained three-dimensional glass-ceramics 15 was measured in the same manner as in Example 1. The maximum value of the maximum R-shape retardation was 1.9 nm / mm. The maximum R-shape haze value was measured and found to be 0.29%.
[0254] <Example 3>
[0255] The glass plate 13 of composition B was chamfered in the same manner as in Example 2, and then crystallized by heat treatment in the same manner as in Example 2, thereby obtaining a microcrystalline glass plate. The obtained microcrystalline glass plate was placed on a convex mold 12 and bent under the same conditions as in Example 2 to obtain a microcrystalline glass in a three-dimensional shape.
[0256] The average curvature radius of the smallest R shape of the obtained three-dimensional glass-ceramics was 5.7 mm, the bending depth was 4.2 mm, and the average curvature radius of the largest R shape was 12900 mm. The haze value of the largest R shape was measured and found to be 3.0%.
[0257] <Examples 4~6>
[0258] Except that the glass composition, crystallization treatment, forming timing, and forming conditions were set as shown in Table 2, the same operation as in Example 2 was carried out to obtain a three-dimensionally shaped microcrystalline glass.
[0259] The results of evaluating the obtained three-dimensional glass are shown in Table 2. In the "Crystallization Treatment Column" in Table 2, when two-step treatment conditions are described, it means that the temperature and time described in the upper section are maintained, and then the temperature and time described in the lower section are maintained. For example, when "750°C-4 hours" is described in the upper section and "920°C-4 hours" is described in the lower section, it means that the temperature is maintained at 750°C for 4 hours, and then the temperature is maintained at 920°C for 4 hours.
[0260] In the "Moulding timing" column, when it is recorded as "before crystallization", it means that the processing is carried out in the order of molding and crystallization. In addition, when it is recorded as "after crystallization", it means that the processing is carried out in the order of crystallization and molding. "Haze value" indicates the haze value after molding and crystallization, and "Δ haze value" indicates the difference between the haze value (Haze) after molding and crystallization and the haze value before molding and crystallization. "Shape deviation" indicates the deviation from the target shape.
[0261] The results of evaluating the obtained glass-ceramics are shown in Table 2. Examples 2 and 4 are examples, and Examples 1, 3, 5, and 6 are comparative examples. The precipitated crystals in Examples 2 to 6 were β-spodumene crystals.
[0262] Table 2
[0263]
[0264] As shown in Table 2, the maximum retardation of Examples 2 and 4 of the three-dimensional shaped glass of the present invention is less than 20 nm, showing high strength and shape stability (molding stability) compared with Example 1 as a comparative example. In addition, the haze value of the largest R shape is less than 1.0%, and the transparency is excellent.
[0265] In addition, compared with Examples 3 and 6 obtained by bending and forming after crystallization, Examples 2 and 4 manufactured by bending and forming amorphous glass that meets the composition range specified in the present invention and then crystallizing can suppress the deterioration of haze caused by heating during forming and achieve high transparency.
[0266] Examples 2 and 4, which were produced by bending amorphous glass satisfying the preferred composition range of the present invention and then crystallizing it, were able to obtain samples with small shape deviations and close to the target shape.
[0267] Therefore, it can be seen that according to the method for producing three-dimensional shaped glass of the present invention, the stress difference generated during forming can be reduced by heat treatment for crystallization to improve strength, and the deterioration of haze can be suppressed to achieve excellent transparency.
[0268] Although the present invention is described in detail and with reference to specific embodiments, various changes or modifications can be made without departing from the spirit and scope of the present invention, which is obvious to those skilled in the art. This application is based on Japanese patent application (Japanese patent application 2019-072736) filed on April 5, 2019, the contents of which are incorporated herein by reference.
[0269] Industrial Applicability
[0270] According to the present invention, it is possible to provide three-dimensional shaped glass having excellent strength, transparency and shape stability and a method for producing the same.
[0271] Description of symbols
[0272] 100 3D Shape Glass
[0273] 110 Center
[0274] 120 Peripheral Department
Claims
1. A glass-ceramic comprising a glass having an average curvature radius of 5.0×10 2 The smallest R shape and average curvature radius of 1.0×10 3 A three-dimensional glass-ceramic having a maximum R shape of more than mm and composed of a plurality of R shapes, wherein The microcrystalline glass is a chemically strengthened glass having a compressive stress layer on the surface, wherein the surface compressive stress value of the microcrystalline glass is 500 MPa or more and the depth of the compressive stress layer is 80 μm or more. The maximum value of the retardation per 1 mm thickness measured by vertically irradiating the center of the smallest R shape with light having a wavelength of 543 nm is 20 nm / mm or less, and The haze value of the largest R shape when converted to a thickness of 0.8 mm is 1.0% or less.
2. The glass-ceramic according to claim 1, wherein: The microcrystalline glass is microcrystalline glass containing β-spodumene crystals.
3. The glass-ceramic according to claim 1 or 2, wherein: The microcrystalline glass contains, in terms of mass % based on oxides: 58%~74% SiO2, 5% to 30% Al2O3, 1% to 14% Li2O, 0~5% Na2O, and 0~2% K2O.
4. The glass-ceramics according to any one of claims 1 to 3, wherein The microcrystalline glass contains, in terms of mass % based on oxides: 58%~74% SiO2, 5% to 30% Al2O3, 1% to 14% Li2O, 0~5% Na2O, 0~2% K2O, 0.5% to 12% in total of any one or more of SnO2 and ZrO2, and 0~6% P2O5.
5. The glass-ceramics according to any one of claims 1 to 4, wherein The light transmittance of the glass-ceramics when converted to a thickness of 0.8 mm is 85% or more.
6. The glass-ceramics according to any one of claims 1 to 5, wherein The microcrystalline glass is used as a protective glass for a display device.
Citation Information
Patent Citations
Production line of ultra-low-expansion microcrystalline glass
CN103058525A
High strength glass-ceramics having lithium disilicate and beta-spodumene structures
CN105683109A
Microcrystal glass product used for electronic equipment cover plate, and microcrystal glass
CN109320091A
Glass production equipment and glass preparation method
CN109369021A
3D cover glass, mold for molding same, and method for manufacturing 3D cover glass
CN109455906A